Teaching Learning Process Of Pancasila And Civic Education At School Of Special Student Sekolah Luar Biasa Negeri 1 Mataram - Hariyanto, Hariyanto; Rispawati, Rispawati; Zubair, Muhammad (Jurnal Pendidikan Sosial Keberagaman, 2024)
Program Study of Pancasila And Civic Education of Faculty Teacher Training and Education as Institution to product of teachers for Junior High School and Senior High School normal student. So that the logical consequence are lecturing, student task, and experience as long as normal student never about disabilities students The existed of individual special need is not separated from the society because they are have same rights for education. So that lecturer and the student of Program Study Pancasila And Civic Education have to understand and have experience of learning teaching for individual special need. Ni’matuzahroh and Nurhamida Yuni (2016: v) said the existed of individual special need never to separated from society because they have same rights of education with normal students. How the important of teaching learning process Pancasila and Civic Education for Special Student School is relevance with policy of Inclusive Education for all by Government. The aims of research are to know: (1) Lesson Plan of Teacher, (2) Teaching Learning Process, (3) Evaluation, and Problem of teaching learning process at class VII, VIII, IX. Methods in this research by qualitative approach with teacher as subject , Head Master and vice curriculum as informant. The data collection are questioner, observation, interview, and document. Data analysis by data reduction, data display, verification and conclusion with data validation. Based on Lesson Plan made of teacher is not Pancasila and Civic Education but integrated by Thematic Lesson. The teaching learning process by scientific approach and class teacher. The scenario of leaching learning process are start with observation, question, try, association, communication, and finished by to stare. The learning evaluation used technique: (1) Attitude by observer and self evaluation, (2) Knowledge by oral test and write test using Reading Text with same questions, and (3) Skill by performance and works product. Problems faced in teaching learning process are difficulties concentration, easy offended, easy hungry, and easy boring. Thematic Lesson Plan in general application for lower class in elementary school. By thematic lesson, the teacher can help the student with fisical. mental, and cognitive disorders. Beside that small class group, the teachers can give attention as long as individual special need. Karen and Wilson (2012) said the teacher inclusive education has to give the student general ability, basic ability, and specific ability.